APLIKASI PENERIMAAN KARYAWAN ONLINE DENGAN FITUR INFORMASI JADWAL TES DAN HASIL KELULUSAN - Aisyah Nuraeni; Siti Sri Hardianti (Universitas Maso'em Bandung, 2019)
In the process of employee recruitment, generally begins with the application process in order to get applicant information so that the company can select employee candidates according to the needs of the company. This process has a long flow and involves prospective employees or applicants, the HRD (Human Resources Department) and the division of each part to carry out the process of information exchange or often called a PIC (Person in Charge). Some of the obstacles that are often experienced are applicant files that are often swapped, lost or scattered, providing timetable information and the results of test evaluations to expensive and uncertain applicants and coordination with slow parts of PIC makes it difficult for companies to get the best candidates and lose the opportunity to save money. Online employee admission applications are offered by researchers as a solution to solve the problem. Functionally the application created can store data and applicant files in the form of softcopy, provide notifications via e-mail, save test results, provide facilities for coordinating schedules and results of PIC evaluations and schedule response facilities. The non-functional system is able to maintain file security, has a graphical interface and is responsive and error handling. In this study used the development of a prototyping system while the Software development used was the Unified process, while the implementation device used the CodeIgniter framework, the programming language PHP and MySQL as the DBMS.